2018
DOI: 10.1021/acschembio.8b00250
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design, Synthesis, and Characterization of the First Irreversible Inhibitor of Focal Adhesion Kinase

Abstract: Focal Adhesion Kinase signaling pathway and its functions have been involved in the development and aggressiveness of tumor malignancy, it then presents a promising cancer therapeutic target. Several reversible FAK inhibitors have been developed and are being conducted in clinical trials. On the other hand, irreversible covalent inhibitors would bring many desirable pharmacological features including high potency and increased duration of action. Herein we report the structure-guided development of the first h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…In accordance with Chen's findings (Yen-Pon et al, 2018), we also discovered small, fully-synthetic covalent binders of FAK C427 via a cysteine-reactive covalent ligand screen using gel-based ABPP against the pure human FAK1 kinase domain ( Fig. S2-S4; Table S2).…”
Section: Main Textsupporting
confidence: 86%
See 1 more Smart Citation
“…In accordance with Chen's findings (Yen-Pon et al, 2018), we also discovered small, fully-synthetic covalent binders of FAK C427 via a cysteine-reactive covalent ligand screen using gel-based ABPP against the pure human FAK1 kinase domain ( Fig. S2-S4; Table S2).…”
Section: Main Textsupporting
confidence: 86%
“…2H). While this manuscript was under revision, an elegant study describing the first structure-guided design, synthesis, and characterization of a FAK1 inhibitor that also covalently targeted C427 of FAK1 and inhibited its function was reported (Yen-Pon et al, 2018). Importantly, this report gives further credence to our hypothesis of the functional relevance of this cysteine and its effects on cancer cell proliferation.…”
Section: Main Textmentioning
confidence: 76%
“…Cys502 in the active site of FAK is known as a key residue for binding with ligands [ 26 ]. This interaction can be found in many X-ray crystallography structures with various inhibitors [ 24 , 27 , 28 , 29 , 30 ]. Moreover, it has been found that three bromine atoms of 14B can form halogen bonds: bromine at C4 with the carbonyl group of Ser568 (3.3 Å) and with the more distant carbonyl group of Asn551 (3.6 Å), bromine at C6 with the carbonyl group of Ile428 (3.6 Å), and bromine at C7 with the carbonyl group of Glu506 (3.7 Å).…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, this cysteine residue could be used as the nucleophilic group for the design of covalent FAK inhibitors. Chen’s group successfully discovered novel FAK inhibitors by the introduction of an acrylamide moiety to the pyrimidine scaffold of TAE-226 in 2018 ( Figure 13 ) [ 90 ]. These compounds with appropriate linkers could ensure that acrylamide group can be in proximity to Cys427 of FAK protein and the 2,4-diphenylamine pyrimidine as a core scaffold to maintain the binding affinity with the FAK protein.…”
Section: The Discovery Of Fak Inhibitors and Their Therapeutic Significancementioning
confidence: 99%
“…Therefore, this cysteine residue could be used as the nucleophilic group for the design of covalent FAK inhibitors. Chen's group successfully discovered novel FAK inhibitors by the introduction of an acrylamide moiety to the pyrimidine scaffold of TAE-226 in 2018 (Figure13)[90]. These compounds with appropriate linkers could ensure that…”
mentioning
confidence: 99%